Old and New Essays on Continuity and Discontinuity in the New Testament - Hooker, Morna D. (Mohr Siebeck, 2024)
This collection of essays by Morna D. Hooker deals with the theme of continuity and discontinuity - primarily between first-century Judaism and early Christianity - and explores the ways in which New Testament writers drew on their own cultures and previous beliefs in interpreting their experience of Jesus.
PublicationDate: 20240430
Keywords: Christology -- Atonement -- Intertextuality -- Exegesis -- Incarnation -- excommunication -- Altes Testament -- Neues Testament